METHODOLOGY OF TEACHING ENGLISH IN NOPHILOLOGICAL HIGHER EDUCATION INSTITUTIONS (Conference Zone, 2022)
In this article, students in non-philological educational institutions will be able to quickly and easily memorize new words and terms learned in a method that encourages students to think more in the process of teaching English, and to identify unknown aspects of the topic. issues of being understandable and interesting to learn and express new knowledge.